Comparative efficacy of postoperative adjuvant transcatheter arterial chemoembolization and hepatic artery infusion chemotherapy in patients with BCLC stage 0-B hepatocellular carcinoma at high risk of recurrence following radical resection - Feng, Xu; Ao, Yupei; Liu, Jiarui; Yuan, Jue; Shi, Zhengrong; Tang, Chengjia (Frontiers in Pharmacology, 2025)
AimThis study aims to compare the efficacy of postoperative adjuvant transcatheter arterial chemoembolization (PA-TACE) and postoperative adjuvant hepatic artery infusion chemotherapy (PA-HAIC) in patients with BCLC Stage 0-B Hepatocellular Carcinoma (HCC) at high risk of recurrence following radical resection.MethodsThis study retrospectively evaluated HCC patients who underwent radical liver resection (LR) at two clinical centers between 1 January 2018, and 31 December 2024. The recurrence-free survival (RFS) and overall survival (OS) were compared among three groups: those who received LR alone, PA-TACE, and PA-HAIC. Propensity score matching (PSM) was applied to minimize inter-group differences and further validate the findings.ResultsA total of 609 patients with high-risk recurrence following radical resection of HCC were included in this study. After PSM, both PA-TACE and PA-HAIC significantly improved median RFS (mRFS) and median OS (mOS) compared with LR alone (mRFS for the LR, PA-TACE, and PA-HAIC groups was 16.5 months, 39.0 months, and 46.0 months, respectively; mOS was 54.0 months, 68.0 months, and not reached for PA-HAIC, respectively). Furthermore, patients treated with PA-HAIC achieved superior mRFS as well as higher 1-year, 2-year, and 4-year RFS rates compared with those treated with PA-TACE. Similarly, PA-HAIC was associated with a significantly longer mOS and a higher 4-year OS rate than PA-TACE. In the construction of the RFS nomogram, the C-indexes for the training and validation cohorts were 0.802 and 0.799, respectively, demonstrating good predictive ability.ConclusionIn HCC patients with high-risk recurrence following radical resection, PA-HAIC significantly improves RFS compared to PA-TACE, but only in patients with MVI, tumor diameter ≥5 cm, or multiple tumors.